Evidence-Based Complementary, Alternative and Integrated Medicine and Efficacy and Safety: Bipolar Disorders - Al-Worafi, Yaser Mohammed; Kifli, Nurolaini; Alsergi, Wafa Mohammed; Ali, Samar Mohammed; Ming, Long Chiau (Taylor & Francis, 2025)
Complementary and Alternative Medicine (CAM) is increasingly recognized as a beneficial adjunct in the prevention and treatment of bipolar disorder, complementing conventional therapies such as mood stabilizers and psychotherapy. CAM approaches, including mindfulness-based cognitive therapy, yoga, acupuncture, light therapy, and nutraceuticals like omega-3 fatty acids, have shown potential in addressing the complexities of bipolar disorder, from mood stabilization to managing comorbid anxiety and depressive symptoms. Despite their promise, the safe and effective use of CAM in bipolar disorder requires a comprehensive, multidisciplinary approach that involves healthcare providers, patients, and caregivers. This includes proper assessment, patient education, monitoring for side effects or interactions with conventional medications, and personalized treatment plans. Furthermore, tailored educational resources are vital for students, educators, healthcare professionals, and researchers to promote the evidence-based integration of CAM into mental health care. Through these educational tools, professionals can stay updated on research advancements, while students and researchers can explore innovative treatments for mood disorders. The collaboration between CAM practitioners and mental health providers ensures holistic care and improves patient outcomes. This chapter emphasizes the importance of evidence-based practices, ongoing monitoring, and patient-centered care when incorporating CAM into bipolar disorder management, contributing to a more holistic and integrated approach to mental health treatment.